2020
DOI: 10.1002/aesr.202000062
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Electrochemical Interface of Oxygen Reduction Electrocatalysts with Ionic Liquids: A Review

Abstract: Hydrogen fuel cells are a promising technology for the environmentally sustainable production of electricity. However, their commercialization is hindered by the sluggish kinetics of the oxygen reduction reaction and by the high cost of the state‐of‐the‐art platinum catalysts. To address these challenges, research has focused on the enhancement of the activity of platinum and platinum group metal (PGM)‐free electrocatalysts, by modifying their composition and topology. Recently, a new approach has emerged to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 139 publications
(394 reference statements)
0
15
0
Order By: Relevance
“…Oxygenophilic and hydrophobic ionic liquids, such as those used as coatings on the surface of electrocatalysts, can modify the triple-point interface, improving oxygen concentration and water expulsion. A recent review by our group has summarized the unexplored potential of ionic liquid layers …”
Section: Bioinspired Interfaces and Mass Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygenophilic and hydrophobic ionic liquids, such as those used as coatings on the surface of electrocatalysts, can modify the triple-point interface, improving oxygen concentration and water expulsion. A recent review by our group has summarized the unexplored potential of ionic liquid layers …”
Section: Bioinspired Interfaces and Mass Transportmentioning
confidence: 99%
“…A recent review by our group has summarized the unexplored potential of ionic liquid layers. 412 Hydrophobicity also has a positive, and perhaps an even more drastic, effect on CO 2 reduction due to (1) the low solubility of CO 2 (33 mM) in aqueous electrolytes causing a mass-diffusion limitation for CO 2 to the electrode surface 413 and (2) the competition with the more thermodynamically favorable HER. In nature, hydrophobicity is utilized to solve these issues; for example, active sites in enzymes such as CODHs/acetyl-CoA synthase are protected by the presence of a hydrophobic protein framework.…”
Section: Nature Offers Several Examples Of How Chemical Compositionmentioning
confidence: 99%
“…In addition, recently, a novel approach based on the use of ionic liquid (IL) such as [BMIM]­[NTf 2 ], [MTDB]­[BETI], [DEMA]­[TfO], etc. to engineer the electrochemical triple-point interface (catalyst–electrolyte–reactant) of both PGM and non-PGM-based catalysts has emerged as a promising alternative under the umbrella of “Solid Catalyst with Ionic Liquid Layer (SCILL)” to boost ORR activity in acidic and alkaline media. The implementation of this approach is to modify the electrocatalysts by coating their inner surface with a controlled amount of ILs, which have attracted special attention in electrochemistry owing to their high ionic conductivity, broad electrochemical window, and good chemical stability . Furthermore, the ILs with fluorinated side chains of the anionic parts are also hydrophobic in nature in addition to having higher O 2 solubility due to the strong affinity of fluorines for oxygen, two desirable properties in ORR electrocatalysts .…”
Section: Introductionmentioning
confidence: 99%
“…This composite material (catalyst + IL) design approach exploits the higher oxygen solubility and hydrophobicity of the IL confined within pores, facilitating a higher frequency of interactions of oxygen with the catalyst surface with simultaneous expulsion of product water . The application of IL has also been shown to increase ORR kinetics through effective suppression of the formation of nonreactive oxygenated species and reduced adsorption of OH intermediates, exposing more active sites available for oxygen adsorption. , Thus, a thin layer of an IL as an additive acts by ensuring high oxygen (reactant) concentration and hydrophobicity (product expulsion) at the active sites in addition to weakening the bond to the OH* intermediate, facilitating overall ORR kinetics. , The enhanced ORR performance of electrocatalysts modified with [BMIM]­[NTf 2 ] has been reported, which was attributed to the hydrophobicity of the IL-suppressing catalyst poisoning by oxygenated species . Qiao et al have reported the improved ORR activity of the nitrogen-doped graphene (GN) electrocatalyst through IL modifications of the interface using 20 wt % (of catalyst wt) of [BMIM]­[NTf 2 ] and [EMIM]­[NTf 2 ] in 0.1 M HClO 4 and 0.1 M KOH .…”
Section: Introductionmentioning
confidence: 99%
“…27 Oxygen solubility results reported in different manuscripts [27][28][29][30][31][32][33][34] display large variations, with a percentage error of up to 60% (Figure S6a). 26 Moreover, to the best of our knowledge, results obtained with different experimental techniques have never been compared in a single study. 27,31,32,35 Most studies neglect the difference between O2 concentration and thermodynamic activity, which is inappropriate for oxygenophilic ionic liquids.…”
Section: Introductionmentioning
confidence: 99%